al-Maslahah al-Mursalah as a source of Islamic law and its relevance to political dispensation - Zakariyah, Luqman (Department of Islamic, Christian and Comparative Religious Studies, Kwara State University, Malete, 2017)
The relevance of Islamic studies to the modern political setting cannot be undermined. This is because Islamic studies covers all aspects of human actions, be it ritual and social. It is observed that publications related to Islamic studies have not explicitly emphasised the relevance of the concept of Maṣlaḥah Mursalah in ’Uṣūl al-Fiqh to the some social sciences enough. Thus, this paper attempts to relate the aforementioned concept to the political science with the view to enunciating the importance, benefit and application of this concept in modern political dispensation. The methodology applied in this paper is content analysis which incorporates both descriptive and prescriptive approaches. The examples used are not exhaustive and limited to the chosen country. The application of the concept may also be found in some Muslim countries without realization.